No Chance to Survive: Mo-CBP3-PepII Synthetic Peptide Acts on Cryptococcus neoformans by Multiple Mechanisms of Action - Tawanny K. B. Aguiar; Felipe P. Mesquita; Nilton A. S. Neto; Francisco Í. R. Gomes; Cleverson D. T. Freitas; Rômulo F. Carneiro; Celso S. Nagano; Luciana M. R. Alencar; Ralph Santos-Oliveira; Jose T. A. Oliveira; Pedro F. N. Souza (MDPI AG, 2023)
Multidrug-resistant Cryptococcus neoformans is an encapsulated yeast causing a high mortality rate in immunocompromised patients. Recently, the synthetic peptide Mo-CBP3-PepII emerged as a potent anticryptococcal molecule with an MIC50 at low concentration. Here, the mechanisms of action of Mo-CBP3-PepII were deeply analyzed to provide new information about how it led C. neoformans cells to death. Light and fluorescence microscopies, analysis of enzymatic activities, and proteomic analysis were employed to understand the effect of Mo-CBP3-PepII on C. neoformans cells. Light and fluorescence microscopies revealed Mo-CBP3-PepII induced the accumulation of anion superoxide and hydrogen peroxide in C. neoformans cells, in addition to a reduction in the activity of superoxide dismutase (SOD), ascorbate peroxidase (APX), and catalase (CAT) in the cells treated with Mo-CBP3-PepII. In the presence of ascorbic acid (AsA), no reactive oxygen species (ROS) were detected, and Mo-CBP3-PepII lost the inhibitory activity against C. neoformans. However, Mo-CBP3-PepII inhibited the activity of lactate dehydrogenase (LDH) ergosterol biosynthesis and induced the decoupling of cytochrome c (Cyt c) from the mitochondrial membrane. Proteomic analysis revealed a reduction in the abundance of proteins related to energetic metabolism, DNA and RNA metabolism, pathogenicity, protein metabolism, cytoskeleton, and cell wall organization and division. Our findings indicated that Mo-CBP3-PepII might have multiple mechanisms of action against C. neoformans cells, mitigating the development of resistance and thus being a potent molecule to be employed in the production of new drugs against C. neoformans infections.